Orange-fleshed sweetpotato (OFSP). Investment guide - Stathers, T.; Mkumbira, J.; Low, Jan W.; Tagwireyi, J.; Munyua, H.M.; Mbabu, A.N.; Mulongo, G. (International Potato Center, 2015)
OFSP investment guide aims to unpack the investment opportunities in the OFSP value chain and offer a decision tool for determining where the key opportunities are and the activities for transforming them, including details on the human, financial and physical resources required. This guide is targeted at national level technical experts in public, private and development institutions, to support them through multisectoral and multi-stakeholder actions to identify and attract investments and implement pro-poor, nutrition-sensitive agricultural growth programmes to reduce vitamin A deficiency.